Religious Experience and Modern Synthetic Religiosity - Raschke, Carl A (Journal of Dharma, 1986)
This article was originally a talk delivered to the national symposium "Revisioning Religious Studies" held in Denver, Colorado and co-sponsored by the Department of Religious Studies and the University of Denver/lliff School of Theology joint Ph.D. programme in the Study of Religion.